Mas Oyama's complete karate course. (New Delhi, India Goodwill Publishing House, 2008)
The world's greatest karate master reveals his philosophy and techniques for practising one of the world's greatest martial arts! Over 1300 photos break down each movement and exercise, and the Mas Oyama himself describes every important aspect of karate-from the basic elements up through set combinations and sparring. There's a technique to build strength, control, precision, and agility in every part of your body.
Fundamentals of Karate -- Application and fundamental techniques -- Kata -- Kumite -- Tameshiwari -- Special applications of karate techniques -- The new karate: modernizing Shiai (competition karate)
"Includes over 1300 photographs" -- book cover
Keywords: Karate